The Functions of The Word Ã¢â¬ÅgetÃ¢â¬Â in Texts - C. Sutarsyah (TEFLIN Journal: A publication on the teaching and learning of English, 1999)
This study investigates the functions of the word Ã¢â¬Ëget and its use in real communication. The main purposes of this study are to find some patterns and collocation of Ã¢â¬Ëget in texts, to find their proportion and to discuss the implication of the study for the teaching of English as a foreign language. For this purpose, a number of data from News Bro (Brown corpus), one of the corpora in the computer, was taken as the main data to be analysed and classified. In order to be more accurate, some other data from News Lob (Lob Corpus) were also taken for comparison. Computer software was used to analyse the data in the form of collocations. The result shows that a number of verb patterns of Ã¢â¬ÅgetÃ¢â¬Â occur more frequently than the others. It also shows that some patterns that are mentioned in the Dictionary do not occur in the data. The result can help teachers of English prepare their teaching material.